New record of Platyrrhinus angustirostris Velazco, Gardner & Patterson, 2010 (Chiroptera, Phyllostomidae) in Colombia and potential distribution (2025)
The systematic revision of the Platyrrhinus helleri clade, which was found to be a species complex, led to the elevation of some subspecies to species level and the description of Platyrrhinus angustirostris Velazco, Gardner & Patterson, 2010. The conservation status and threats to this species are currently poorly understood. We report a new record of this species, extending its distribution into west-central Colombia. We used WorldClim bioclimatic layers to model its potential distribution; the results indicate that areas with stable temperatures and substantial precipitation during the warmest quarter offer the best environmental suitability for this species. This information is important for the conservation of P. angustirostris and its tropical habitats.